Silent or silenced? Minority ethnic students and the battle against racism. Issue 5 (3rd September 2022) - Wong, Billy; Copsey-Blake, Meggie; ElMorally, Reham
ABSTRACT: Racism is harmful for minority ethnic students from compulsory to tertiary education. Whilst there appears to be renewed public interest in structural racism, the realities of lived racism are, for many, a part of everyday life. This paper explores the experiences of minority ethnic students in UK higher education, especially their approaches to racism and coping strategies. Drawing on 51 in-depth interviews, the authors discuss the different ways in which racism can affect students and the extent to which it is normalised. As a means of coping, students appear to develop different degrees of emotional detachment and desensitisation towards racist behaviours. They discuss how white privilege in higher education can contribute to the silencing of minority ethnic students in the battle against racism, especially in white university spaces where racist behaviours are generally accepted, overlooked or trivialised. They conclude with a discussion of implications for policy and practice.